" مدى تطبيق مبادئ الحوكمة في مؤسسات التعليم العالي من وجهة نظر أعضاء هيئة التدريس" دراسة حالة في جامعة صبراتة: كلية الاقتصاد والعلوم السياسية – كلية الإدارة والموارد البشرية (Comprehensive Journal of Science, 2026)
The study aimed to identify the extent of applying governance principles in higher education institutions from the point of view of faculty members in Libyan universities. To achieve the study objectives, the descriptive analytical approach was followed, where a questionnaire was distributed to faculty members at Sabratha University in the Faculties of Economics and Political Science - Sorman, and Management and Human Resources - Zliten. The data were analyzed using the statistical analysis program (Spss). The study reached several results, the most important of which are: There is a clear weakness in the level of application of governance principles within Sabratha University, as well as the weakness of the laws in force in the event of violations such as bribery, fraud and misuse of power. The study recommended enhancing the university's efforts in applying governance principles by developing clear strategies and increasing employees' awareness of the importance of these principles in improving institutional performance.
Keywords: Governance principles - Financial and administrative corruption - Higher education institutions